Zwitterionic PMCP‐Modified Polycaprolactone Surface for Tissue Engineering: Antifouling, Cell Adhesion Promotion, and Osteogenic Differentiation Properties. Issue 42 (25th August 2019) - Chen, Xingyu; Lin, Zaifu; Feng, Ying; Tan, Hong; Xu, Xinyuan; Luo, Jun; Li, Jianshu
Abstract: Biodegradable polycaprolactone (PCL) has been widely applied as a scaffold material in tissue engineering. However, the PCL surface is hydrophobic and adsorbs nonspecific proteins. Some traditional antifouling modifications using hydrophilic moieties have been successful but inhibit cell adhesion, which is not ideal for tissue engineering. The PCL surface is modified with bioinspired zwitterionic poly[2‐(methacryloyloxy)ethyl choline phosphate] (PMCP) via surface‐initiated atom transfer radical polymerization to improve cell adhesion through the unique interaction between choline phosphate (CP, on PMCP) and phosphate choline (PC, on cell membranes). The hydrophilicity of the PCL surface is significantly enhanced after surface modification. The PCL‐PMCP surface reduces nonspecific protein adsorption (e.g., up to 91.7% for bovine serum albumin) due to the zwitterionic property of PMCP. The adhesion and proliferation of bone marrow mesenchymal stem cells on the modified surface is remarkably improved, and osteogenic differentiation signs are detected, even without adding any osteogenesis‐inducing supplements. Moreover, the PCL‐PMCP films are more stable at the early stage of degradation. Therefore, the PMCP‐functionalized PCL surface promotes cell adhesion and osteogenic differentiation, with an antifouling background, and exhibits great potential in tissue engineering. Abstract : A multifunctional PCL‐PMCP film is prepared with the properties of antiprotein adsorption and promoting cell adhesion. Bone marrow mesenchymal stem cells proliferation on this film is remarkably improved, and osteogenic differentiation is detected, even without adding any osteogenesis‐inducing supplements. Moreover, the PCL‐PMCP films are more stable at the early stage of degradation.